Penggunaan Metode Suku Kata dalam Meningkatkan Kemampuan Baca Anak Kelas I di MI Islamiyah Kedungjambe Tahun Pelajaran 2024/2025 - Susanti, Rizky Dwi Ari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2025)
The lack of reading ability among 1st-grade students at MI Islamiyah Kedungjambe focuses on the use of the syllable method, supporting and inhibiting factors, and the results of using the syllable method in improving the reading ability of 1st-grade students at MI Islamiyah Kedungjambe. This study uses a qualitative approach. The subjects of this research are 19 students of the 1st grade at MI Islamiyah Kedungjambe. The research employs data collection techniques such as interviews, observations, and documentation. The results of this study include the development of syllable methods that positively assist students who have difficulty reading. There are several steps and preparations in using this method, such as the teacher arranging/combining consonant letters and vowel letters, and preparing media in the form of markers and a whiteboard as part of the preparation. There are several supporting and hindering factors in the use of syllable methods; one of them is the interest in reading within the students, and hindering factors from within the students, such as lack of attention. The results of using the syllable method are very helpful, as evidenced by the scores obtained before and after using the syllable method, which increased from 30% to 70% in training students to read well and correctly.